Analysis of Short-Term Prestress Losses in Post-tensioned Structures Using Smart Strands - Sang-Hyun Kim; Sung Yong Park; Sung Tae Kim; Se-Jin Jeon (International Journal of Concrete Structures and Materials, 2022)
Abstract The proper estimation of prestressing force (PF) distribution is critical to ensure the safety and serviceability of prestressed concrete (PSC) structures. Although the PF distribution can be theoretically calculated based on certain predictive equations, the resulting accuracy of the theoretical PF needs to be further validated by comparison with reliable test data. Therefore, a Smart Strand with fiber optic sensors embedded in a core wire was developed and applied to a full-scale specimen and two long-span PSC girder bridges in this study. The variation in PF distribution during tensioning and anchoring was measured using the Smart Strand and was analyzed by comparison with the theoretical distribution calculated using the predictive equations for short-term prestress losses. In particular, the provisions for anchorage seating loss and elastic shortening loss were reviewed and possible improvements were proposed. A new method to estimate the amount of anchorage slip based on real PF distributions revealed that the general assumption of 3–6-mm slip falls within a reasonable range. Finally, the sensitivity of the PF distribution to a few of the variables included in the equation of the elastic shortening loss was examined. The study results confirmed that the developed Smart Strand can be used to improve the design parameters or equations in PSC structures by overcoming the drawbacks of conventional sensing technologies.